Studying the recurrent diagrams of carbon monoxide concentration at early ignitions in premises - Pospelov, Boris; Andronov, Vladimir; Rybka, Evgenіy; Meleshchenko, Ruslan; Borodych, Pavlo (Eastern-European Journal of Enterprise Technologies, 2018)
It was shown that the methods of nonlinear dynamics, surpassing traditional methods of temporal, frequency or frequency-temporal analysis of dangerous ignition factors may be used for early detection of ignitions in premises. The existence of carbon monoxide in gas medium was found to be most dangerous at fires in premises. The theoretical grounds for studying recurrent diagrams of carbon monoxide concentration in gas medium were substantiated. The modification of recurrent distance diagrams, based on power representations was proposed, making it possible to highlight selectively or to smooth structural features of configuration of recurrent points of distance diagrams. Results of research into recurrent diagrams of dynamics of carbon monoxide concentration show that the specified factor of ignition of materials has generally not stochastic, but chaotic dynamics. It was qualitatively determined that dynamics of carbon monoxide concentration in gas medium has non-uniformed distribution of points. In this case, the configuration of clustering of recurrent points of diagrams for various flammable materials varies and can be used for detecting the type and the beginning of early ignition of combustible material. The established fact of chaotic dynamics of carbon monoxide concentration in gas medium at early ignition of materials should be taken into consideration in the development of new technologies for reliable detection of early ignitions in premises. The data, obtained in the research, are important for deeper understanding of dynamics of the process of carbon monoxide formation in gas medium in non-airtight premises at ignition of various materials, because it is related to saving lives of people who are in these premises and their timely evacuation.